Perlis Muslim-friendly tourism as special interest tourism - Saad, Mazni (Borneo Tourism Research Centre (BTRC), Faculty of Business, Economics & Accountancy (FBEA), & Universiti Malaysia Sabah (UMS), 2024)
This study delves into the perceptions of Perlis tourism operators regarding Perlis Muslim Friendly Tourism, intending to assess its potential to attract more tourists to the state. Specifically, it aims to evaluate the views of tourism operators regarding the idea of proposing Perlis Muslim Friendly Tourism. Despite its advantageous location near popular destinations like Langkawi Island and Thailand, Perlis significantly trails other Malaysian states in tourism development. This study gathers insights through an online survey, garnering responses from 22 participants. The findings reveal a mixed perception of Perlis Muslim Friendly Tourism, yet an overall positive inclination toward the concept. Furthermore, the study identifies several gaps that impede Perlis' tourism growth. It emphasizes the necessity for close collaboration between the Perlis state government and the Perlis Islamic Religious and Malay Customs Council (MAIPS) to address these challenges effectively and unlock the state's untapped tourism potential. Through concerted efforts, Perlis can leverage its unique assets and strategic location to emerge as a thriving tourist destination in Malaysia.